Penerapan Aplikasi Android “Menyusui Asi-Q” pada Ibu Menyusui di Wilayah Kerja Puskesmas Kota Palembang - Virgian, Kharisma; Setiawati, Desy; Veratiwi, Veratiwi; Franciska, Yunetra; Hakim, Dwi Ratnawaty (Jurnal Pengabdian kepada Masyarakat (ABDIKEMAS), 2023)
The success of exclusive breastfeeding is determined by many factors, namely from the family, environment, health workers and the mother herself. Internal factors of the mother are the lack of knowledge about exclusive breastfeeding and the lack of awareness of the mother to provide exclusive breastfeeding. This community service activity is the result of research activities that have been carried out before. The results of the research were applied in the Implementation of the ASI-Q Breastfeeding Android Application for breastfeeding mothers in the work area of the Talang Ratu Palembang Health Center. This activity aims to apply the android application "Breastfeeding ASI-Q" to breastfeeding mothers so that it can increase maternal knowledge, facilitate the breastfeeding process and reduce anxiety in breastfeeding mothers. This activity is carried out by conducting counseling activities for breastfeeding mothers at the Anggraini Posyandu. Before counseling, a pre-test was carried out to determine the level of knowledge of mothers about breastfeeding. After counseling, mothers can access applications at home and combine them in one Whattsaap group as a medium of communication and media for questions and answers. After one month of using the app, breastfeeding mothers filled out the post test link. With the ASI-Q breastfeeding application, mothers can breastfeed happily, the milk will come out smoothly so that the baby will always be healthy and cheerful. From the results of the evaluation obtained in this activity, breastfeeding mothers said that this application is very useful, educative and informative so that it can increase the insight of breastfeeding mothers how the ins and outs of breastfeeding.